Intravenous doxycycline, azithromycin, or both for severe scrub typhus - Varghese, GM; Dayanand, D; Gunasekaran, K; Kundu, D; Wyawahare, M; Sharma, N; Chaudhry, D; Mahajan, SK; Saravu, K; Aruldhas, BW; Mathew, BS; Nair, RG; et al. (Massachusetts Medical Society, 2023)
BACKGROUND: The appropriate antibiotic treatment for severe scrub typhus, a neglected but widespread reemerging zoonotic infection, is unclear.